“Constructing selfhood and otherness in the East-West context" - Bryla, Martyna Marika (My University, 2018)
Since his debut in 2002, Gary Shteyngart, a Russian-American author of Jewish extraction has not only garnered popularity among readers, but also inspired critical interest from reviewers and scholars. While Shteyngart’s talent for satire and his idiosyncratic, fast-pace style of writing undoubtedly account for his popular success, the critics are invariably drawn to the thematic threads that drive his first three novels and bloom in his latest autobiographical work. Among these, there is construction of immigrant identity on the threshold of three cultures, the search for and the development of the writerly voice, and the representation of selfhood and otherness within the East-West context. Accordingly, in this paper I will address these main threads within Shteyngart’s works, focusing particularly on the second one. Drawing on imagology, I will situate Shteyngart’s body of work at the intersections between identity and culture, in order to analyse the role of emotional geographies and cultural maps in his development as a three-culture writer.
Keywords: Shteyngart, Gary - Crítica e interpretación; Gary Shteyngart; East; West; Imagology; Immigration